THE IMPLEMENTATION OF VILLAGE MINISTER’S REGULATION NUMBER 21 OF 2015 ABOUT THE DETERMINATION OF VILLAGE FUND USE PRIORITY IN FISCAL YEAR OF 2017 (A Case Study in Karangrejo Village of Kerjo Sub District of Karanganyar Regency) - Nita Janurizky Aris Tri Haryanto, Sri Riris Sugiyarti (Solidaritas, 2018)
ABSTRACT Karangrejo village successfully prioritizes community development and empowerment so that its successfulness process can be guidelines or can inspire other villages. This research aims to describe and to analyze the statement about the compatibility of Village Fund Implementation based on Village Minister’s Regulation (Permendes) Number 21 of 2015 about the Determination of Village Fund Use Priority,The result of analysis showed that the implementation of village fund use priority in community development and empowerment based on Permendes No.21 of 2015 has run well, but the objective expected by the community has not been achieved maximally, as indicated with the plan implemented less compatible to the community’s desire, implementation and reporting quickness level affected by resource and the relationship to other institution is established with supervisor only rather than all institution, organization establishment and job division has not been clear and executor team coordination is not inadequate as indicated with the meeting held any time the change occurs, community responds positively because it contributes effort and fund positively to community development and empowerment and executor team understand the implementation of prioritized village fund.Through community development and empowerment, this study recommends the training for human resources to be held to give them understanding on the ever changing policy to be implemented. In its implementation, Sekdes (Village Secretary) and Bendes (Village Treasurer) should understand community fund increase coming from fund income and expenditure to relieve the community’s burden in development policy implementation. Keywords: Implementation, Development Priority, Village Fund